Techno-economic assessment of dry fermentation in household biogas units through co-digestion of manure and agricultural crop residues in Egypt. (April 2020) - Samer, Mohamed; Abdelaziz, Salwa; Refai, Mohamed; Abdelsalam, Essam
Abstract: In rural Egypt, communities face multiple challenges such as insufficient infrastructures for waste treatment, limited access to cheap energy and poor soils fertility. A decentralized, low-tech biogas technology for combined waste treatment and energy production, anaerobic digestion can achieve many sustainable development goals and resolve many issues faced by rural communities, treating and stabilizing organic waste into high-quality biofertilizer. Household biogas units for rural communities, however, should be subjected to techno-economic assessment to confirm their feasibility and technical efficiency. Therefore, this paper conducted: (1) survey of household biogas units and agricultural crop residues in rural communities in Egypt, (2) technical study of household biogas units, and (3) financial economic study. The results can be summarized as follows: (1) complete set of technical data on biogas units were documented, (2) crop residues were mapped using GIS software, (3) financial feasibility results were discussed. The total revenues were 1716.01, 2574.02, 3432.02, and 5148.04 EUR for the household biogas unit with the capacity of 2, 3, 4, and 6 m 3, respectively. It was concluded that the units available in rural Egypt are considered as profitable projects from the profitability perspectives, and the values of the profitability indicators increased as the unit size increased. Highlights: Survey of biogas units and agricultural wastes in rural communities was conducted. Complete set of technical data on biogas units were documented. Crop residues were mapped using GIS software. Biogas units available in rural communities were found profitable projects. Profitability increases as the size of the biogas unit increases.